2003
DOI: 10.1002/ppsc.200390002
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Descriptors for Particle Shape Characterization

Abstract: Conventional shape descriptors, formed from a ratio of two particle size measurements, are among the simplest of the many methods used for quantitative particle shape characterization. However, a significant limitation of using one of these shape descriptors is that its value is often not unique to a specific shape. Use of several different shape descriptors may circumvent this problem but, as particle size can be defined in a large number of ways, a similarly large number of shape descriptors can be defined. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(73 citation statements)
references
References 26 publications
(30 reference statements)
0
72
0
1
Order By: Relevance
“…The aspect ratio is defined as the ratio between length to breadth of the circumferential rectangle with minimal area [52,55,56]. The separation into sub-sets of spheroids and non-spherical, irregularly shaped particles by other criteria does not strongly vary, i.e., roundness threshold of >0.75 (>0.85) and aspect ratio threshold of <1.18 (<1.07) leads to about the same sub-sets of particles.…”
Section: Classification Schemementioning
confidence: 99%
“…The aspect ratio is defined as the ratio between length to breadth of the circumferential rectangle with minimal area [52,55,56]. The separation into sub-sets of spheroids and non-spherical, irregularly shaped particles by other criteria does not strongly vary, i.e., roundness threshold of >0.75 (>0.85) and aspect ratio threshold of <1.18 (<1.07) leads to about the same sub-sets of particles.…”
Section: Classification Schemementioning
confidence: 99%
“…The shapes of particles of different materials produced in laboratorial and industrial scales are often regarded as being arbitrary. Despite this degree of arbitrariness, previous research has demonstrated that the ratios of various particle size measurements can be used to derive shape descriptors of different orders (Hentschel & Page, 2003;Pourghahramani & Forssberg, 2005). However, the challenge lies in determining the combinations of size measurements that best provide the relevant morphological information of a sample or some samples.…”
Section: Introductionmentioning
confidence: 99%
“…Each of such combinations is sensitive to a specific attribute of shape according to the size measurements selected. Based on this principle, the size measurements obtained by the PVS 830 were combined as follows to create 85 new shape descriptors (Hentschel & Page, 2003):…”
Section: Physical Descriptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should also be noted that, while there are many possible shape measures already available in the literature, and many more that can be designed, they are not all independent. Some analysis on this topic was carried out by Hentschel and Page [23] who computed the correlations between many similar measures as well as determining the most effective for the specific task of powder particle analysis.…”
Section: D Shape Measures For Computer Visionmentioning
confidence: 99%